Pulmonary arterial hypertension after atrial septal defect closure: a case report - Lucia Kris Dinarti; Dyah Wulan Anggrahini; Muhammad Reyhan Hadwiono; Abdul Majid Halim Wiradhika; Vera Dewanto; Anggoro Budi Hartopo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
Most patients with congenital heart disease (CHD) who underwent successful shunts defect repair can be remained asymptomatic for years. It leads to a high number of losses to follow-up after patients discharge. After closure, pulmonary hypertension (PH) prevalence seems to be high and associated with increased morbidity and mortality. We reported a 55 y.o. female diagnosed with pulmonary arterial hypertension (PAH) and atrial fibrillation (AF) 31 years after atrial septal defect (ASD) closure by surgery, who never had routine follow-up evaluation because she remained asymptomatic for years. Physical examination revealed heart enlargement with irregular rhythm and pan systolic murmur in the fourth left sternal border. Electrocardiogram showed AF normal ventricular response, right axis deviation and suggestive for right ventricular hypertrophy. Laboratory testing found the NT pro-BNP level was 2,476 pg/mL. The chest X-ray showed enlargement of the heart and was representative of PH. From echocardiography study, transthoracic and transoesophageal echocardiography, we found no sign of residual shunt. There were right atrial and right ventricular dilatation, severe tricuspid regurgitation (TR) and a high probability of PH with TR velocity of 4.46 m/s. Right heart catheterization concluded mean pulmonary arterial pressure 46 mmHg, flow ratio 1.1, and pulmonary artery resistance index 15.5 Woods unit.m-2. We highlight this case because of the high incidence of PH long after defect closure. The high number of lost to follow-up patients can lead to morbidity and mortality.